Pengaruh Pendidikan Kesehatan Dengan Booklet Terhadap Pengetahuan Ibu Hamil Tentang Anemia Kehamilan Di Puskesmas Kotabaru - Shinta Mardiana; Hartinah Hartinah; Ika Friscila; Aida Fitriani (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Anemia during pregnancy can result in pregnancy complications as well as negative effects on the growth and development of the fetus in the womb, potentially causing death of the mother and child. In order to prevent and treat anemia, various programs can be started. One of them is increasing the knowledge of pregnant women using interesting media. The aim of the research was to analyze the effect of health education with booklets on pregnant women's knowledge about pregnancy anemia at the Kotabaru Community Health Center. The research method uses descriptive analysis with pre-post test. The research sample consisted of 30 people divided into 2 groups, namely control and intervention. Bivariate analysis using Wilxocon and Mann Whitney. The results statistical tests showed that the booklet influenced the knowledge scores of pregnant women in the Kotabaru health center working area with the post test average difference between the treatment group and the control group being p = 0.001 (<0.05).